Revisiting Jesus's House - Doole, J. Andrew (Journal for the study of the New Testament, 2026)
Did Jesus have a house in Capernaum? In this article I revisit the proposal that the earliest Gospel tradition knew of Jesus being ?at home?, and suggest that only a particular exegetical inference from the narratives of the Gospels of Mark and Matthew lead to the view that Jesus is staying in Simon Peter's house. The Gospel tradition developed ideas of Jesus as itinerant and "homeless", or as the constant dinner guest or otherworldly visitor to earth. Jesus was by no means a wealthy property-owner, but he did have a place to live in Capernaum, where he brought people and where others came to see him. The beginnings of the Jesus "movement" were actually stationary, based for the most part in Jesus's house in Capernaum.